Comparative Study of Intrusion Detection System - Chowdhary, Mahak; Suri, Shrutika; Bhutani, Mansi (International Journal of Computer Sciences and Engineering, 2014)
In past few decades, there has been rapid progress in internet based technology and application areas for computer networks have emerged. But number of attacks on network has increased dramatically due to which interest of researchers in the network intrusion detection has also increased. Intrusion detection is a type of security management system for computers and networks. An intrusion detection system gathers and analyzes information from various areas within computer or network to identify possible security breaches, which include both intrusion and misuse. Intrusion detection system also helps in detecting anomalies in network traffic. Intrusion Detection system follows a two-step process. The first procedures are host-based and are considered the passive component, these include: inspection of the system`s configuration files to detect inadvisable settings; inspection of the password files to detect inadvisable passwords; and inspection of other system areas to detect policy violations. The second procedures are network-based and are considered the active component: mechanisms are set in place to reenact known methods of attack and to record system responses. Aim of this research paper is to review current trends in intrusion detection system and analyze current problems that exist in this area. Some key features, attacks detected by different types of IDs are explained in this paper.